2020
DOI: 10.1111/jcmm.15612
|View full text |Cite
|
Sign up to set email alerts
|

Acriflavine targets oncogenic STAT5 signaling in myeloid leukemia cells

Abstract: Acriflavine (ACF) is an antiseptic with anticancer properties, blocking the growth of solid and haematopoietic tumour cells. Moreover, this compound has been also shown to overcome the resistance of cancer cells to chemotherapeutic agents. ACF has been shown to target hypoxia‐inducible factors (HIFs) activity, which are key effectors of hypoxia‐mediated chemoresistance. In this study, we showed that ACF inhibits the growth and survival of chronic myeloid leukaemia (CML) and acute myeloid leukaemia (AML) cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, activating the P21 Waf1 protein, an important marker of cellular senescence, was reported at a low concentration of ACF, suggesting that ACF might also induce a senescent phenotype in CML cells. Finally, ACF showed positive effects in IM-resistant CML cells sensitization, suggesting that ACF might be a useful drug that could be used alone or in combination with IM in order to alleviate resistant cells [75]. In summary, ACF presents a promising therapeutic strategy against CML, by inhibiting both HIF-1 and STAT5 transcription factors, and by eradicating TKI-resistant leukemia cells.…”
Section: Acf As An Anti-leukemic Agentmentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, activating the P21 Waf1 protein, an important marker of cellular senescence, was reported at a low concentration of ACF, suggesting that ACF might also induce a senescent phenotype in CML cells. Finally, ACF showed positive effects in IM-resistant CML cells sensitization, suggesting that ACF might be a useful drug that could be used alone or in combination with IM in order to alleviate resistant cells [75]. In summary, ACF presents a promising therapeutic strategy against CML, by inhibiting both HIF-1 and STAT5 transcription factors, and by eradicating TKI-resistant leukemia cells.…”
Section: Acf As An Anti-leukemic Agentmentioning
confidence: 88%
“…In 2011, a study showed that ACF inhibited chronic lymphoblastic leukemia (CLL) cell survival and proliferation [52]. Our team recently demonstrated a cytotoxic effect of ACF on MV-4-11 cell line, a current model for acute myeloid leukemia (AML) cells [75]. This is also in agreement with a study by Sabolova et al, who showed that ACF induces a dose-dependent inhibition of proliferation of HL-60 AML cell line and L1210 mice leukemia cells [76].…”
Section: Acf As An Anti-leukemic Agentmentioning
confidence: 99%
See 3 more Smart Citations